A proof of concept infant-microbiota associated rat model for studying the role of gut microbiota and alleviation potential of Cutibacterium avidum in infant colic - Rocha Martin, Vanesa Natalin; Del’Homme, Christophe; Chassard, Christophe; Schwab, Clarissa; Braegger, Christian; Bernalier-Donadille, Annick; Lacroix, Christophe (Frontiers in Nutrition, 2022)
Establishing the relationship between gut microbiota and host health has become a main target of research in the last decade. Human gut microbiota-associated animal models represent one alternative to human research, allowing for intervention studies to investigate causality. Recent cohort and in vitro studies proposed an altered gut microbiota and lactate metabolism with excessive H2 production as the main causes of infant colic. To evaluate H2 production by infant gut microbiota and to test modulation of gut colonizer lactose- and lactate-utilizer non-H2-producer, Cutibacterium avidum P279, we established and validated a gnotobiotic model using young germ-free rats inoculated with fecal slurries from infants younger than 3 months. Here, we show that infant microbiota-associated (IMA) rats inoculated with fresh feces from healthy (n = 2) and colic infants (n = 2) and fed infant formula acquired and maintained similar quantitative and qualitative fecal microbiota composition compared to the individual donor’s profile. We observed that IMA rats excreted high levels of H2, which were linked to a high abundance of lactate-utilizer H2-producer Veillonella. Supplementation of C. avidum P279 to colic IMA rats reduced H2 levels compared to animals receiving a placebo. Taken together, we report high H2 production by infant gut microbiota, which might be a contributing factor for infant colic, and suggest the potential of C. avidum P279 in reducing the abdominal H2 production, bloating, and pain associated with excessive crying in colic infants.